Komposisi Tanaman Agroforestri Dan Kontribusinya Terhadap Pendapatan Rumah Tangga Di Desa Pesawaran Indah Kabupaten Pesawaran Lampung - Marlica Tri Asmi; Rommy Qurniati; Dwi Haryono (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
Agroforestry is a land use management system by combining agriculture and forestry and or husbandry to achieved yield optimalization (Indriyanto, 2006). Agroforestry systems with mixed garden pattern consist various types of plants that perform a different composition of plants so there are varied incomes from one place to another. This study aims to: (1) identifying the composition of agroforestry based on INP and its effect on income, (2) analyze the composition of the contribution of agroforestry products to total farm household income. Methods of data collection for species composition using purposive sampling while for the respondent farmers using stratified random sampling. Data analysis using quantitative descriptive analysis method. The results showed that the largest contributes of the composition of plant in three zones, namely the upper, middle, and bottom obtained on the composition of IX which is located in the lower zone of Rp 23,127,404, -/ha/yr with highest INP of cocoa is 94.86%. The magnitude of the average farmer's total income from each source of income from agroforestry to Rp 36.992.171/ha/yr and non-agroforestry amounting to Rp 9.312.500/yr. The magnitude of the contribution of agroforestry systems to farmers' incomes Pesawaran Indah Villages of 91.44%, meaning that agroforestry provides a major contribution to the household income of farmers. Keywords: agroforestry, composition of plants, contribution of agroforestry